Dynamic analysis of coupling misalignment and unbalance coupled faults - Haifei Wang; Junjie Gong (Journal of Low Frequency Noise, Vibration and Active Control, 2019)
Misalignment is a common fault occurring in the rotor system. However, the response characteristics have not been understood comprehensively, especially the relation between forces or torques and displacements, accelerations, or moments. First, misalignment modeling is investigated in this paper. Two coupled rotor system is modeled by six degrees of freedom. Misalignment effects are considered at coupling location using nodal force vectors and moment vectors. Second, Newmark- β method is used to solve the nonlinear equations. Acceleration, displacement, and force or moment response characteristics are discussed. Some results are obtained as follows: (1) 2× will appear in the parallel misalignment forces spectrum, and 0× will appear in the vertical force spectrum; 2×, 4×, 6× will appear in the angular misalignment moment spectrum. (2) In parallel misalignment simulation, it is found that multifrequency components are more obvious, static components are showed in vertical forces and displacements, 1× is dominated and 2× is weak in the displacement spectrum, and 2× is obvious in the force spectrum; acceleration is periodic impulse signal and 1× and 2× are dominated in its spectrum; vertical displacement is truncated and its values are positive, the orbit looks like an inverted triangle. (3) In angular misalignment simulation, it is found that multifrequency components of response are more obvious, 2× is obvious in the vertical displacement spectrum, and 2× is dominated in the moment spectrum; acceleration is periodic impulse signal, horizontal and vertical displacements are periodic, the orbit looks like a moon or an eight shape, and 2× is obvious in the moment spectrum.